Daya Hambat Ekstrak Etanol Batang Lakum (Cayratia trifolia (L.) Domin) Terhadap Pertumbuhan Isolat Phytophthora sp. Im5 secara In Vitro - Rikhsan Kurniatuhadi, Fitrie Dwi Lestari Elvi Rusmiyanto PW (Universitas Tanjungpura, 2018)
Stem rot disease is caused by one of Phytophthora pathogenic fungi that attacks several types of cultivated plants. The alternative control against Phytophthora attack can be done with the use of natural fungicides. One of the herbs that can be untilized is the ethanol extract of lakum stem (Cayratia trifolia (L.) Domin). The aim of this research is to know the effect of ethanol extract of lakum stem and its secondary metabolite in inhibiting the growth of isolate Phytophthora sp. Im5. The research was conducted for three months starting from October to December 2017. This research used solid dilution method and completely randomized design (CRD) wth 8 levels of treatments, i.e. positive control, negative control, ethanol extract concentration of 5, 10, 15, 20, 25 and 30 mg/ml. The test for secondary metabolite compounds was done by phytochemical screening method. The result showed that the concentration of 30 mg/ml has the biggest antifugal activity with the inhibition percentage of 34.98%. The activity of lakum stem ethanol extract against isolate Phytophthora sp. Im5 was included in moderate catagory. The results of phytochemical screening showed that the ethanol extract of lakum stem contained alkaloid, flavonoid and tannin compounds.